Ваше преуспевание - в ваших руках!: [Сборник: Перевод] / Д. Карнеги, Л. Питер, С. Паркинсон, А. Блох (Республика, 1993)
Экземпляры: (20230911) / Инвентарный номер: 23100 / Цена: 800.00 / Сис.шифр: 88.49 / Авт.знак: В23 / ББК: 88.49